The Genetic Algorithm is used to extract the parameters of a solar cell from a current-voltage characteristic - Eshwaran; Ramulu (The journal of contemporary issues in business and government, 2019)
In order to evaluate the performance of a solar cell and to extract the highest amount of output power feasible from the cell, it is essential to determine the characteristics of the solar cell. A computationally based binary-coded genetic algorithm (GA) is proposed in this study for extracting the parameters (I0, Iph, and n) for a single diode solar cell from its current-voltage (I-V) characteristic using the current-voltage characteristic. Utilizing LabVIEW as a programming tool, the technique was developed and tested by applying it to an I-V curve created from the literature and using reported data. It was shown to be effective. Using GA, we were able to acquire values for parameters that were in excellent agreement with previously published values for silicon and plastic solar cells. modify as follows: "After the program's validation, it was used to the extraction of parameters for an experimental I-V characteristic of a 4 x 4 cm2 polycrystalline silicon solar cell measured at less than 900 W/m." The I-V characteristic derived using GA is very similar to the experimental one in all respects.